2010
DOI: 10.1007/s00384-010-1091-6
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted versus open surgery for rectal cancer: a meta-analysis of randomized controlled trials on oncologic adequacy of resection and long-term oncologic outcomes

Abstract: The meta-analysis suggests that there are no differences between laparoscopic-assisted and open surgery in terms of number of lymph nodes harvested, involvement of CRM, local recurrence, 3-year overall survival, and disease-free survival for rectal cancer. However, more high-quality studies are needed for further analysis due to the small number of included studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 41 publications
5
67
0
9
Order By: Relevance
“…Importantly, analysis of the RCTs included in our study indicated that LPS surgery had similar oncological outcomes to open surgery in terms of OS and disease-free survival [6,8,11,12,14]. Moreover, previous meta-analyses also demonstrated that LPS surgery offered equivalent oncological outcomes to open surgery [18][19][20][21][22][23]. Further studies are needed to validate these results.…”
Section: Discussionsupporting
confidence: 58%
“…Importantly, analysis of the RCTs included in our study indicated that LPS surgery had similar oncological outcomes to open surgery in terms of OS and disease-free survival [6,8,11,12,14]. Moreover, previous meta-analyses also demonstrated that LPS surgery offered equivalent oncological outcomes to open surgery [18][19][20][21][22][23]. Further studies are needed to validate these results.…”
Section: Discussionsupporting
confidence: 58%
“…For rectal cancer, 9 phase III randomized clinical trials 11,20,21,[33][34][35][36][37][38][39][40][41][42] and 7 meta-analyses were selected. 28,29,[43][44][45][46][47] No meeting abstracts satisfied the inclusion criteria. The main design characteristics of each randomized trial are summar ized in Table 2 for colon cancer and in Table 3 (Table 1).…”
Section: Researchmentioning
confidence: 99%
“…A recent meta-analysis by Huang et al [3] to assess the oncologic adequacy of resection and the oncologic outcomes after laparoscopic versus open surgery for rectal cancer showed that laparoscopic surgery is comparable to open surgery in terms of anatomopathological findings and the local recurrence rate, although no data about the prognostic role of lymphadenectomy were given. To our best knowledge, no clinical trials have analyzed the risk factors for local recurrence, disease-free survival, and overall survival after laparoscopic TME for extraperitoneal rectal cancer over a 5-year minimum follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Developed and popularized by Heald and co worker [1], total mesorectal excision (TME) is presently the surgical gold standard, with a 4 % local recurrence rate and a 78 % tumor-free survival rate in curative cases at 5 years [2]. A recent meta-analysis by Huang et al [3] of randomized controlled trials that included small numbers of patients with upper or mid-to-low rectal cancer did not show differences between laparoscopic and open surgery in terms of the number of lymph nodes (LN) harvested, local recurrence, 3-year disease-free survival, and overall survival. Although a minimum of 12 LN in the…”
mentioning
confidence: 99%